2016
DOI: 10.1016/j.ydbio.2015.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Novel α-tubulin mutation disrupts neural development and tubulin proteostasis

Abstract: Mutations in the microtubule cytoskeleton are linked to cognitive and locomotor defects during development, and neurodegeneration in adults. How these mutations impact microtubules, and how this alters function at the level of neurons is an important area of investigation. Using a forward genetic screen in mice, we identified a missense mutation in Tuba1a α-tubulin that disrupts cortical and motor neuron development. Homozygous mutant mice exhibit cortical dysgenesis reminiscent of human tubulinopathies. Motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 63 publications
(69 reference statements)
10
58
3
Order By: Relevance
“…The Tuba1a ‐S140G mutation impairs the ability of α‐tubulin to bind GTP, which disrupts tubulin heterodimer formation and reduces the functional tubulin pool (Keays et al, ). The Tuba1a ‐N102D substitution also destabilizes the heterodimer and impairs incorporation of mutant Tuba1a into the microtubule lattice (Gartz Hanson et al, ). However, the divergent neurodevelopmental and behavioral phenotypes associated with the heterozygous S140G and N102D mutant mice suggest that these variants may impact neuronal microtubule function via several differing mechanisms, not solely through loss‐of‐function.…”
Section: Mouse Models Provide Insight Into Tubulinopathy‐associated Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tuba1a ‐S140G mutation impairs the ability of α‐tubulin to bind GTP, which disrupts tubulin heterodimer formation and reduces the functional tubulin pool (Keays et al, ). The Tuba1a ‐N102D substitution also destabilizes the heterodimer and impairs incorporation of mutant Tuba1a into the microtubule lattice (Gartz Hanson et al, ). However, the divergent neurodevelopmental and behavioral phenotypes associated with the heterozygous S140G and N102D mutant mice suggest that these variants may impact neuronal microtubule function via several differing mechanisms, not solely through loss‐of‐function.…”
Section: Mouse Models Provide Insight Into Tubulinopathy‐associated Mmentioning
confidence: 99%
“…Tuba1a-N102D homozygous mice have dramatic defects in brain development including abnormal cortical lamination and reduction in the size of olfactory bulbs, indicative of impaired neuronal migration (Gartz Hanson et al, 2016). In contrast, Tuba1a-N102D heterozygous mice are viable, undergo normal cortical lamination, and do not exhibit any evidence of neuronal migration errors (Gartz Hanson et al, 2016). From a mechanistic standpoint, Tuba1a-R215*, -S140G and -N102D variants are all predicted to reduce the levels of functional Tuba1a, despite the observed difference in heterozygous phenotypes (Bittermann et al, 2019;Gartz Hanson et al, 2016;Keays et al, 2007).…”
Section: Mouse Models Provide Insight Into Tubulinopathy-associatedmentioning
confidence: 99%
“…The reduced incorporation of the mutant tubulin into microtubules appears to be compensated by a corresponding increase in Tub3 incorporation in the tub1 G437R mutant, and explains the reliance of tub1 G437R mutant cells on Tub3 expression. Previous studies estimated that Tub3 accounts for roughly ~10-30% of the cell's α-tubulin content (Bode et al, 2003;Gartz Hanson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…6D). It is interesting to note that one of these studies (Gartz Hanson et al, 2016) observed a ~17% increase in the rate of microtubule polymerization that was dependent on the presence of a wild-type copy of Tub3. This suggests that the increased proportion of Tub3 in the mutant microtubules may be partially responsible for the altered dynamicity observed here (16% increase in polymerization rate; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation